2020
DOI: 10.1097/md.0000000000020983
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery on multiple clinical outcomes

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 85 publications
0
33
0
1
Order By: Relevance
“…Our study showed the importance in adopting the ERAS protocols to improve perioperative outcomes of RC patients compared to a traditional approach and that the multimodal nature of ERAS is better than individually focusing on a single element within it. A recent umbrella review of 23 meta-analyses across multiple surgical specialties including urology (3) by Zhang et al 34 showed strong evidence that ERAS pathways can reduce LOS and cost without increasing morbidity and readmission. Despite these positive results, we need to exercise caution in interpreting these findings, there are limitations that cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the importance in adopting the ERAS protocols to improve perioperative outcomes of RC patients compared to a traditional approach and that the multimodal nature of ERAS is better than individually focusing on a single element within it. A recent umbrella review of 23 meta-analyses across multiple surgical specialties including urology (3) by Zhang et al 34 showed strong evidence that ERAS pathways can reduce LOS and cost without increasing morbidity and readmission. Despite these positive results, we need to exercise caution in interpreting these findings, there are limitations that cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…ERAS protocols are complex, requiring organised care from a multidisciplinary team to ensure strong patient outcomes and provide an elevated level of care. Enhanced recovery pathways reduce length of stay (LOS) by an average of 2.35 days and total cost by an average of $639.06 in comparison with conventional perioperative procedures, according to a 2020 meta-analysis of ERAS across multiple surgeries and surgical specialties [1]. Despite concerns, ERAS does not increase morbidity, mortality or readmission rates [2], having even been shown to decrease 30-day mortality rates following orthopedic surgery [1].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced recovery pathways reduce length of stay (LOS) by an average of 2.35 days and total cost by an average of $639.06 in comparison with conventional perioperative procedures, according to a 2020 meta-analysis of ERAS across multiple surgeries and surgical specialties [1]. Despite concerns, ERAS does not increase morbidity, mortality or readmission rates [2], having even been shown to decrease 30-day mortality rates following orthopedic surgery [1]. Since its beginnings as 'fast-track' surgery in 1997 [3], ERAS has been researched across a broad range of surgical subspecialties, from orthopedics to transplant surgery [4].…”
Section: Introductionmentioning
confidence: 99%
“…Innovations to address these include specific therapeutic interventions, such as fluid management 5 , and broader interventions through models or systems of care which combine high quality elements, such as enhanced recovery after surgery (ERAS) 6 , and prehabilitation programmes 7 . Systems changes perhaps provide a greater opportunity for measurable improvements 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, detailed high-quality cost-effectiveness analysis is relatively limited in systems or models of care in postoperative care. For example, in a recent ERAS umbrella systematic review 6 , only 13 of over 200 studies even mentioned cost as an outcome. Those studies that do address cost and effectiveness frequently including simple estimates, or formal but simple cost-effectiveness calculations [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%